Genetic divergence among accessions of Arachis repens based on vegetative morphological traits - José Marlo Araújo de Azevedo (Revista Brasileira de Zootecnia, 2011)
The objective of this study was to verify the existence of genetic variability among accessions of Arachis repens based on vegetative morphological characters, identifying those which contribute least for distinction of those accessions. Nineteen accessions were evaluated in a completely randomized design with ten replicates, established in 4-m² plots. The traits evaluated were: basal leaflet length, basal leaflet width, apical leaflet length, apical leaflet width, petiole length, internode average length and internode diameter. The data obtained were submitted to univariate statistical analysis and accessions were grouped by the Scott-Knott test, at 1% of probability. The analysis of canonical variables and Tocher method were used to study the genetic divergence among accessions. Six heterogeneous groups were formed by Tocher method and eight groups were formed by technique of canonical variables, in which a consistency among grouping set by the different techniques used was observed. There is genetic divergence among accessions of A. repens on the basis of vegetative morphology traits, but there is the need to extend variability in Banco Ativo de Germoplasma de Amendoim Forrageiro (Active Germplasm Bank of Forage Peanut). Apical leaflet length is the trait that contributes least to the accessions' distinctions, but it is important to maintain the standard cluster, and it should not be discarded